SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SANTRI TELADAN PADA MADRASAH DINIYYAH ROUDLOTUL QUR’AN DENGAN MENGGUNAKAN METODE TOPSIS - Sholihah , Niswatus; Mufarrihah , Iftitaahul; Widoyoningrum , Sri (Inovate, 2023)
This research designs and implements a decision support system (DSS) for determining model students. The purpose is to overcome the fading enthusiasm for learning among students due to repetitive daily activities and to maximize the effectiveness of the educational program that has been designed. Used topsis method as the rank algorithm, this studied evaluates the extent to which students excel in both accepting and implementing the educational program. The results of the conducted analysis show that the system is capable of automatically determining rank based on the input data for each criterion. Based on the input data, the obtained results indicate that Nadia Roudhotul H achieves a score of 0.9971, followed by K Salma Aziza with a score of 0.9892. And the third rank is Yutnia Fatimah with a score of 0.9871. Keywords: DSS, Model Students, TOPSIS.